The Role of Perceived Social Interaction, Perceived Enjoyment, Perceived Utility, and Self-Presentation in Mediating Social Presence on Purchase Intention - Qadri, Rizni Aulia; Sinambela, Fitriana Aidnilla; Marcella, Kenny (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
The focus of the research is to observe and find out the impact that occurs between Perceived Social Interaction, Perceived Enjoyment, Perceived Utility, and Self-Presentation with purchase intention with social presence mediation. Indonesia is one of the countries with the highest number of e-commerce transactions in Southeast Asia. As technology develops, features emerge that make buying and selling activities easier. This feature allows sellers to market their goods directly via live video, so consumers only need to follow the seller's live video and buy the goods they need. Data collection techniques in this research include using questionnaires and literature studies. The subjects of this research are customers who make purchases via live broadcasts in Batam. The sampling technique for this research is random sampling. The data analysis method used in this research is quantitative analysis. The objects of this research were 355 samples who had shopped for fashion via live-stream. Sampling was selected randomly. Variables are measured using a Likert scale. The data testing stage starts from outer loading, average variance extracted, composite reliability. cronbach alpha, path coefficient, specific indirect effect, r squared adjusted. From the research conducted, it was found that perceived enjoyment, perceived utility, self-presentation, and social presence have a positive and significant influence on purchase intentions. However, perceptions of social interaction do not influence purchase intentions.